2016
DOI: 10.1038/srep32318
|View full text |Cite
|
Sign up to set email alerts
|

Blood B Lymphocyte Stimulator (BLyS)/BAFF levels may reflect natural immunity to HIV in highly exposed uninfected Beninese Commercial Sex Workers

Abstract: We have previously shown that excess B lymphocyte Stimulator (BLyS)/BAFF in plasma and on surface of blood dendritic cells (DC) of HIV-infected progressors coincides with B-cell dysregulations and increased frequencies of “precursor” innate marginal zone (MZ)-like B-cells. In contrast, both blood BLyS levels and frequencies of this population remained unaltered in HIV elite-controllers. Based on these observations, we hypothesized that control of BLyS and innate B-cell status could be associated with natural i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 46 publications
4
35
2
Order By: Relevance
“…Elucidating the underlying mechanisms of immunological deficits in HIV-1-infected children will help in designing effective interventional strategies. Earlier studies have reported defects in DCs leading to alterations in B cell subsets in HIV-1-infected individuals ( 30 , 35 , 43 , 44 ). An inverse correlation between BLyS (BAFF) released by mDCs and B cell numbers has been shown during primary HIV-1 infection ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elucidating the underlying mechanisms of immunological deficits in HIV-1-infected children will help in designing effective interventional strategies. Earlier studies have reported defects in DCs leading to alterations in B cell subsets in HIV-1-infected individuals ( 30 , 35 , 43 , 44 ). An inverse correlation between BLyS (BAFF) released by mDCs and B cell numbers has been shown during primary HIV-1 infection ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information on phenotypic and functional defects of DCs, B cells and DC mediated alterations in B cell subsets in pediatric HIV-1 infection and disease progression ( 15 , 17 , 25 , 27 , 28 , 35 , 36 ). Independent studies have reported lower percentages of DCs and linked DC-mediated alterations of B cell subsets with faster disease progression ( 32 ), while preservation of HIV-1 specific memory B cells is associated with efficient viral neutralization in elite controllers (ECs) ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Study subjects and sample processing Cryopreserved peripheral blood mononuclear cells (PBMCs) were obtained from a study of commercial sex workers in Cotonou, Benin. HIV-1-infected women were enrolled from a sexworker clinic and HIV-1-uninfected women were enrolled from a general health clinic, as described previously [49,50]. PBMCs were obtained from 20 untreated HIV-infected women, 20 HIV-infected women receiving ART and 10 healthy women (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest an association between elevated plasma BAFF and APRIL levels and hypergammaglobulinemia in HIV-infected individuals (95-99) ( Table 2). Hypergammaglobulinemia appears to be a result of a dysregulated blood B cell compartment characterized by the BAFF-induced expansion of MZ B cells (97,(100)(101)(102). Dendritic cells, monocytes, and macrophages are the sources of increased BAFF and APRIL levels during HIV infection (97, 99, 101, 103) ( Fig.…”
Section: Viruses Hivmentioning
confidence: 99%